Insecurity as Impedinment to National Development - Salihu Ibrahim; MAM Sameem (STIM LASHARAN JAYA MAKASSAR, 2023)
Recent historical narrative of Nigeria has been largely filled with the question of insecurity. Every part is faced with the menace of security challenges that have made life miserable and National development elusive. The paper looked at the menace of insecurity across the country and analyzed its implication on the development of the nation. It is found that insecurity is a harbinger of underdevelopment. Using qualitative approach the paper benefits from desk review of literature. The paper is significant as it illuminates on the dangers of insecurity to the socio-economic development of the nation. It will also add to the pool of existing works on the subject matter of insecurity and national development